تأثير الـ pH على بعض الخصائص البيولوجية لأفراد النوع longispina O.F. Müller Daphnia من متفرعات القرون (Cladocera – Daphniidae ) في الشروط المخبرية - ياسين قصاب, محمد; زيـني, أديـب; ديـب, ديــم (Latakia University Journal -Biological Sciences Series, 2019)
تمت الدراسة على أفراد النوع القشري O.F. Muller Daphnia longispina عالمي الانتشار، وهو هدف للاستزراع ويستخدم كغذاء حي ليرقات الأسماك والقشريات في المزارع السمكية، حيث تم الحصول على الدفعة الأولى منها من بعض الأوساط المائية العذبة القريبة كسد السخابة وسد الحفة، وتم أقلمتها في المختبر تمهيداً لإجراء سلسلة من التجارب المخبرية عليها، حدّد فيها تأثير درجات مختلفة من الـ pH (6- 7,5 – 8,5 – 9,5 ) على بعض الخصائص البيولوجية للنوع كمعدل النمو الطولي والوزني والفترة الزمنية التي تسبق طرح أول حضنه ومعدل عدد الحضنات ومعدل عدد البيض التي تضعها الأنثى الواحدة خلال مدة التجربة، ومدة حياة الأنثى. استمرت التجربة من 1/3/ 2010 ولغاية 1/5/2010 م. بّينت النتائج أن قيم درجة الـ pH المناسبة لحياة أفراد هذا النوع تقع بين 7,5- 8,5 والتي يمكن اعتمادها أثناء تجارب الاستزراع مستقبلاً. The Study was conducted on Daphnia longispina O.F. Muller which is cosmopolitan species and a goal for the cultivation as live food for larval fish and crustaceans in fish farms. The first batch of these Crustaceans ,which collected from the nearest fresh water bodies as Al-skhabh , Al-Haffa Reservoirs, have been adapted them in the laboratory conditions to preparation them to a series of Experiments, and select the effects of different degrees of the pH ( 6,7.5,8.5,9.5) on some biological characteristics as longevity, growth rates , the age at first reproduction, number of broods, number of eggs by a single female during the period of the experiment, and the rate of mortality of the female. Experiment lasted from 01/03/2010 until 05/01/2010. The results showed that the degree of the pH suitable for the life of Daphnia longispina lies between 7.5 to 8.5, which can be adapted during Daphnia's cultivation in the future.